Urban growth and water access in sub-Saharan Africa: Progress, challenges, and emerging research directions - (:unkn) unknown (My University, 2017)
For the next decade, the global water crisis remains the risk of highest concern, and ranks ahead of climate change, extreme weather events, food crises and social instability. Across the globe, nearly one in ten people is without access to an improved drinking water source. Least Developed Countries (LDCs) especially in sub-Saharan Africa (SSA) are the most affected, having disproportionately more of the global population without access to clean water than other major regions. Population growth, changing lifestyles, increasing pollution and accelerating urbanization will continue to widen the gap between the demand for water and available supply especially in urban areas, and disproportionately affect informal settlements, where the majority of SSA's urban population resides. Distribution and allocation of water will be affected by climate-induced water stresses, poor institutions, ineffective governance, and weak political will to address scarcity and mediate uncertainties in future supply. While attempts have been made by many scientists to examine different dimensions of water scarcity and urban population dynamics, there are few comprehensive reviews, especially focused on the particular situation in Sub-Saharan Africa. This paper contributes to interdisciplinary understanding of urban water supply by distilling and integrating relevant empirical knowledge on urban dynamics and water issues in SSA, focusing on progress made and associated challenges. It then points out future research directions including the need to understand how alternatives to centralized water policies may help deliver sustainable water supply to cities and informal settlements in the region.
Keywords: African Research